Los adultos mayores como demandados subsidiarios en los juicios de alimentos y sus incidencias socio-jurídicas en el cantón Machala. Proyecto de reforma al numeral 1 de art. innumerado 5 de la ley reformatoria al código de la niñez y adolescencia. - Pineda Machuca, Edison Enrrique. (2014)
In the State Constitutional Rights and Justice, families are at the core of the State are protected by the Constitution of Ecuadorians. In our country it is easy to overlook everything concerning the violation of rights, that is why I made this research that trying to put a solution to the violation of the rights of the elderly without affecting the interests of children and adolescents, for which we express that the principal obligation in food lies with the parents who are the parent-child, but not others in the case of unnumbered article 5 states such as grandparents, brothers and uncles, for which many times is put aside his constitutional rights and the international rights of the elderly.he statute provides that a subsidiary must have and must have full knowledge and consent with your signature and rubric that takes on the responsibility. However in trials of foods in which to demonstrate the absence, incapacity, lack of resources or the principal disability, the obligation falls on the subsidiary required without them being aware and give their consent to this obligation, in many cases are not even aware of the existence of minors by those who claim food. Conducted an analysis of the legal, social and economic situation of the subsidiary called forced, established in paragraph 1 of Art unnumbered 5 of the Code for Children; which in most cases they are elderly people and not always retirees. Finally he made a legal, critic and social analysis of the illegal transfer of duties and responsibilities, protected by constitutional guarantees, besides a comparative analysis between the interests of the child and the right of so-called forced subsidiary.